“Comparative Evaluation of Clinical Application of Monolithic and Folding Implants in Rehabilitation of Elderly Patients with Various Degrees of Atrophy of Alveolar Processes - Bhadane, Vaibhav; Tembhurne, Jyoti; Gangurde, Arti; Chauhan, Manish; Jaiswal, Niraja; Akulwar, Ravikumar (Journal of Coastal Life Medicine, 2023)
Aim: The long-term success rates of single-stage and two-stage surgeries including dental implantation with monolithic and collapsible implants for the rehabilitative treatment of elderly patients were compared and contrasted. Materials and methods: Sixty individuals, ages 60 to 70, with a wide range of dentition defect diagnoses, were observed in clinical settings. The research used mechanical oscillatory - resonance, statistical analysis, implant placement using the ART IMPLANT system's non-removable implants, placement of a fixed interim prosthesis, and immediate occlusal functional load are all part of the single-stage surgical procedure. Results: Using a single-stage protocol of dental implant surgery and non-detachable implants considerably reduced the time required for surgical phases of treatment and full rehabilitation (p 0.05). Conclusions: Therefore, it is important to highlight the system's therapeutic application, To rehabilitate the jaws of elderly patients with variable degrees of alveolar process atrophy, a single-stage surgical approach including the use of non-detachable (monolithic) dental implants has been developed.